Menangkal Potensi Radikalisme Sejak Dini melalui Penyelenggaran Bimbingan Konseling dalam Pendidikan Tingkat Dasar - Ida Fitri Shobihah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2018)
Elementary education is the first formal level of education for children. Students in primary education aged 6-12 years who are psychologically included in the age category of the child. The age of the child is a crucial stage of development because it is included in the early stages of development which are vulnerable and highly influenced by their environment. One of the things that can damage a child's development is the potential for radicalism from an early age. Therefore, the presence of a counseling guidance program in primary education becomes very important, in order to help overcome the potential of radicalism in the development of children. This research will examine further about how the form of potential radicalism in children in schools studied and the holding of counseling guidance (BK) in primary education in an effort to overcome the potential for radicalism in children. The study was conducted using a mix method. The results showed that the form of potential radicalism in children in the form of understanding and negative attitudes towards non-Muslims. the madrasas studied showed the low potential of radicalism due to the provision of counseling guidance.The Potential of Radicalism